ANALISIS CITRA MEREK, KUALITAS PELAYANAN, KUALITAS PRODUK DITINJAU KEPUASAN PELANGGAN CAFE BELIKOPI BANDAR KEDIRI - Ana, Wahyu Rizki; Samari; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2023)
Cafe Belikopi is a coffee shop located in Bandar Kediri Village. In the observation, researchers found problems, namely brand image, service quality, and product quality. The purpose of this study was to find out how the influence between brand image, service quality, and product quality at Cafe Belikopi Bandar Kediri. The variables used are (1) Brand Image (2) Service Quality (3) Product Quality (4) Customer satisfaction. The sample collection method used in this study was to use a purposive sampling technique with a total of 40 respondents. The approach and analysis technique used in this study is multiple linear analysis with SPSS 23. Based on the results of the study (1) brand image has a significant effect on customer satisfaction (2) service quality has a significant effect on customer satisfaction (3) product quality has a significant effect on customer satisfaction, and (4) brand image, service quality, product quality, and customer satisfaction have a significant effect on customer satisfaction at Café Belikopi Bandar Kediri.